1999
DOI: 10.1046/j.1365-2621.1999.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave phase control heating

Abstract: Food processors are increasingly looking towards new microwave-based technologies to deliver competitive advantage in the market place, reduce operational costs, allow greater product innovation and increase flexibility without the need for large capital investments. The technical barriers to the widespread exploitation of microwave heating, and opportunities for microwave heating in food processing, are discussed in the context of the need to understand the microwave field/material/process interaction. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Several systems dealing with the direct control of product heating have been investigated (Bows et al 1999;Gerling 2000). To this respect, the interference of electromagnetic waves (IEW) was employed in order to obtain uniform temperature profiles during heating.…”
Section: Introductionmentioning
confidence: 99%
“…Several systems dealing with the direct control of product heating have been investigated (Bows et al 1999;Gerling 2000). To this respect, the interference of electromagnetic waves (IEW) was employed in order to obtain uniform temperature profiles during heating.…”
Section: Introductionmentioning
confidence: 99%
“…Bows et al . (1999) , Fritz (1988) and Lau & Sheppard (1990) showed that this is readily achieved with travelling wave single mode applicators, where it was possible to generate many different heating patterns at any instant in time.…”
Section: Classification Methodologymentioning
confidence: 99%
“…Bows et al . (1999) described a travelling wave waveguide system to generate conditions for vector addition heating, where the heating pattern in various materials was controlled by changing the phase of one microwave signal relative to the other.…”
Section: Development and Validation Of The Classification Systemmentioning
confidence: 99%
See 2 more Smart Citations